2010
DOI: 10.1038/oby.2009.421
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Alginate on Satiation, Appetite, Gastric Function, and Selected Gut Satiety Hormones in Overweight and Obesity

Abstract: Lack of control of food intake, excess size, and frequency of meals are critical to the development of obesity. The stomach signals satiation postprandially and may play an important role in control of calorie intake. Sodium alginate (based on brown seaweed Laminaria digitata) is currently marketed as a weight loss supplement, but its effects on gastric motor functions and satiation are unknown. We evaluated effects of 10 days treatment with alginate or placebo on gastric functions, satiation, appetite, and gu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(56 citation statements)
references
References 40 publications
(43 reference statements)
3
50
1
1
Order By: Relevance
“…Using only structured clinical questionnaires would therefore be inappropriate to evaluate these patients especially whenever bariatric treatment has to be considered. Moreover, in accordance with previous observations [15,16] the EE prevalence in our asymptomatic obese patients was not negligible (10/20) and not significantly lower than non-obese GERD patients (12/15) and obese GERD patients (6/15).…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Using only structured clinical questionnaires would therefore be inappropriate to evaluate these patients especially whenever bariatric treatment has to be considered. Moreover, in accordance with previous observations [15,16] the EE prevalence in our asymptomatic obese patients was not negligible (10/20) and not significantly lower than non-obese GERD patients (12/15) and obese GERD patients (6/15).…”
Section: Discussionsupporting
confidence: 94%
“…The differences between the groups are significant when p<0.05; NS not significant findings were lacking in the other investigated groups and surprisingly in all the obese patients without symptom distinction. These findings could be due to different motility abnormalities in the upper digestive tract, recently demonstrated in obesity by means of manometry and MII [6,7,11,15]. The presence of hiatal hernia, especially larger than 3 cm, can also jeopardize the LES function and enhance esophageal acid clearance [3].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…These hormonal effects may primarily be related to ghrelin and insulin and possibly cortisol [33, 35]. …”
Section: Meal Frequencymentioning
confidence: 99%
“…However, the literature has been inconsistent when it comes to whether viscosity directly slows gastric emptying. In certain studies, the viscosity did not slow gastric emptying (14,15); in other studies, the viscosity delayed the GER (16,17). Hoad et al (18) reported no difference in gastric emptying between a control guar gum and an intragastric gelling stimulus but did find different fullness scores.…”
Section: Introductionmentioning
confidence: 97%